2018
DOI: 10.1101/402107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In SilicoIdentification of Three Types of Integrative and Conjugative Elements (ICEs) inElizabethkingia anophelisStrains Isolated from Around the World

Abstract: 27Elizabethkingia anophelis is an emerging global multidrug-resistant opportunistic pathogen. 28 We assessed the diversity among 13 complete genomes and 23 draft genomes of E. anophelis 29 derived from various environmental settings and human infections from different geographic 30 regions around the world over past decades from 1950s. Thirty-one of these 36 strains harbor 31 integrative and conjugative elements (ICEs). A total of 52 ICEs were identified, and 32 categorized into three ICE types based on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…This transposon element inserted into and disrupted the gene MutY (an adenine DNA glycosylase that is required for fixing G‐A mis‐pairs), making the strain more liable to mutation and outbreak infection (Perrin et al, ). Recent research showed that ICEs were ubiquitous in E. anophelis species; 31 of selected 36 E. anophelis strains (86%) harbored 32 ICEs (Xu, Pei, Nicholson, Lan, & Xia, ). These ICEs were classified into three types: ICEEaI, ICEEaII, and ICEEaIII.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This transposon element inserted into and disrupted the gene MutY (an adenine DNA glycosylase that is required for fixing G‐A mis‐pairs), making the strain more liable to mutation and outbreak infection (Perrin et al, ). Recent research showed that ICEs were ubiquitous in E. anophelis species; 31 of selected 36 E. anophelis strains (86%) harbored 32 ICEs (Xu, Pei, Nicholson, Lan, & Xia, ). These ICEs were classified into three types: ICEEaI, ICEEaII, and ICEEaIII.…”
Section: Resultsmentioning
confidence: 99%
“…For example, conjugative elements ICEEaII and ICEEaIII were identified in the Singapore outbreak strain NUHP1. Also, the Anopheles mosquito strains Ag1 and R26 contained ICEEaIII (Xu et al, ). More detailed analysis of ICEs will clarify pathogenesis and drug resistance mechanisms of E. anophelis .…”
Section: Resultsmentioning
confidence: 99%